Intercalação de lítio na heteroestrutura Janus WSSe/Siliceno - Cintra, Gabriel Borelli (2024)
In this dissertation, a theoretical study is presented through computer simulations based on the density functional theory (DFT) to investigate the electronic and structural properties of the WSSe/Silicene heterostructure and its applicability as an electrode for a lithium ion battery. To achieve this, the lithium interaction with each monolayer was examined, indicating a symbiotic relationship in the formation of the heterostructure, resulting in electronic and structural characteristics conducive to energy storage. The conducted calculations reveal that (1) the formation of the heterostructure is an exothermic process, yielding a conductive material, (2) lithium adsorption is energetically favorable with binding energies on the order of 3.0 eV for the heterostructure, exhibiting a metallic character in the obtained structure, (3) the energy barrier for ion diffusion is on the order of 0.34 eV, (4) the open-circuit voltage measured with ion concentration variation ranged from 1.29 to 1.02 V, decreasing with increasing concentration. Based on the obtained results, the studied heterostructure possesses suitable characteristics for an anode material